Towards Effective Foreign Language Teaching: Focus on Dyslexia - Botwina, Renata (Verbum, 2011)
This paper aims to overview the problems faced by dyslexic students learning a foreign language in the theoretical framework of foreign language teaching methodology (Berninger and Wolf 2009, Crombie 2010, Stasiak 2004, etc.) and psychology (Gardner 1983, 1999, Bogdanowicz 2002, 2004, Davis 1997, etc) The author of the paper is going to prove that dyslexic students benefit from the use of multisensory techniques (VAK) which stimulate their learning process by engaging students at multiple levels of perception. Special attention is given to the nature of dyslexia, its types and handicaps it results in. Numerous solutions to the problem are presented and analysed within the framework of Gardner’s theory of Multiple Intelligences (MIT), which seeks to explore each student’s strong intelligences to deal with those weaker ones. Accordingly, dyslexic students and their teachers should be challenged to recognise the hidden potential of dyslexia and see it as a gift to be explored. Moreover, the importance of safe classroom environment has been stressed, as once a dyslexic student feels comfortable in the classroom, the teacher can equip him with a range of techniques and strategies to deal with dyslexia successfully. In addition, a significant role of the teacher and parents in the process of teaching dyslexics is discussed. Finally, the author of the paper gives a number of practical tips how to deal with dyslexia and proves that foreign language teaching (FLT) can be both effective and enjoyable for those who encounter this handicap.
Keywords: dyslexia; foreign language teaching; learner-based instructions; low-stress environment; multi-sensory stimulation; motivation.